Remoção de poluentes em um sistema de alagados construídos atuando como pós-tratamento de efluente de reator UASB e de filtro biológico percolador - Jocilene Ferreira da Costa (2013)
One method of treating domestic wastewater for potential use in small communities is the treatment in constructed wetlands. In the experiment, two units of subsurface horizontal flow constructed wetlands arranged in parallel were used and filled with blast furnace slag, similar to the particle size of crushed stone # 1. Each of the units has been designed to treat a flow of 7.5 m³.d-1, equivalent to a population of approximately 50 people each, for the post-treatment of domestic wastewater by UASB reactor and open biological trickling filter (FBPA). The system was installed at the Center for Research and Training in Sanitation - CePTS / UFMG / COPASA, located in Arrudas WWTP in the city of Belo Horizonte Brazil. The dimensions of each unit were: lengtj 24.1 m; width 3.0 m; filter bed height 0.4 m; liquid height 0.3 m. One unit was planted with Typha latifolia (cattail) respecting a minimum density of 4 plants per m2. When necessary, periodic pruning was carried out. The other unit was not planted, serving as a experimental control. The wastewater received preliminary treatment, consisting of fine screening and grit removal. Samples were collected weekly or fortnightly in the raw sewage, effluent from UASB reactor and open trickling filter and in the effluent from the planted and unplanted wetlands.Fortnightly samples were also collected at 03 different points along the length of the wetlands. To evaluate systems performance, the following variables were quantified: chemical oxygen demand (COD), biochemical oxygen demand (BOD), total nitrogen, phosphorus, dissolved oxygen, alkalinity, pH, temperature, redox potential and electrical conductivity. To evaluate the growth of cultivated plants and their influence on the performance of the planted unit, cattail samples were evaluated by measurements of plant height. To characterize the composition of plant, biomass was collected at the shoot for the quantification of dry matter and nitrogen and phosphorus. The evapotranspiration was measured in evaporimetric tanks. Statistical analysis for comparison between the vegetated and non-vegetated unit was performed by nonparametric comparison of dependent variables, with paired samples, by the Wilcoxon test at a significance level of 5%, using the Statistica ® software. The results showed a significant improvement in effluent quality. In Phase 1 (treatment of the effluent from the UASB reactor), the average effluent concentrations of BOD, COD and TSS from the planted and not planted units were 25 and 23 mg L-1, 50 and 55 mg L-1, 9 and 6 mg.L-1 respectively. For Phase 2 (treatment of the effluent from a system comprised by UASB reactor and open trickling filter), the mean effluent concentrations for planted and not planted units were also very low, for BOD (13 and 12 mg.L-1), COD (26 and 31 mg L-1) and TSS (16 and 12 mg L-1). TKN and N-ammonia in Phase 2 showed values of final average concentrations lower than in Phase 1, about 22 mg L-1 and 23 mg L-1 TKN and 19 mg.L-1 and 20 mg.L-1 for N-ammonia for the planted and unplanted units, respectively. The average final concentrations of phosphorus in Phase 1 was 2.3 mg.L-1 and in Phase 2 of 1.3 mg.L-1 for both units. In terms of loads removed in the first phase were statistically significant only for total nitrogen removal efficiency, with 12.4% for planted unit and 16.0% for unplanted unit. In Phase 2 there was statistically significant difference for the parameters COD, BOD, TSS, total N and total P. The removal efficiencies based on loads were higher in the planted unit for COD (80 and 76%), TKN (38 and 33%) and N ammonia (37 and 32%). The root of Typha latifolia had nutrient concentrations similar to the shoot (results from last sampling), with values of 16.5 g.kg-1 N and 4.1 g.kg-1 P in the root. It was observed that the removal efficiency in the wetland units was little affected by changing the characteristic of the effluent arising from the UASB reactor and open trickling filter, except for N-ammonia, TKN, total-P, which were higher in the treatment of the effluent from the trickling filter. The foliar portion had 24.1 g N.kg-1 and 4.4 g P. kg-1. No impact of precipitation on the removal efficiency of pollutants was found. No major impacts of evapotranspiration were observed in the removal efficiency of N and P. Measurements of the longitudinal profile of the concentration of COD indicated continual decay along the length, with similar behavior in both units. Despite the various positive aspects, it should be noted that, after four years, there was clogging, leading to substantial runoff in both units.In general, and based on the results of this long-term monitoring, it can be concluded that horizontal subsurface flow constructed wetland systems are a very good alternative for the post-treatment of anaerobic and aerobic effluents. It is believed that this system, due to the good results and the relatively long duration of the test is ready to be used for small-scale communities.